Bottom-Up Copper Filling of Millimeter Size Through Silicon Vias. Issue 1 (12th January 2019) - Josell, D.; Menk, L. A.; Hollowell, A. E.; Blain, M.; Moffat, T. P.
Abstract : This work demonstrates void-free Cu filling of millimeter size Through Silicon Vias (mm-TSV) in an acid copper sulfate electrolyte using a combination of a poloxamine suppressor and chloride, analogous to previous work filling TSV that were an order of magnitude smaller in size. For high chloride concentration (i.e., 1 mmol/L) bottom-up deposition is demonstrated with the growth front being convex in shape. Instabilities in filling profile arise as the growth front approaches the free-surface due to coupling with electrolyte non-uniform hydrodynamics. The reentrant notches at the bottom of the TSVs caused by intentional over-etching during fabrication negatively impact the filling results. In contrast, deposition from low chloride electrolytes (i.e., 80 μmol/L) proceeds with a passive-active transition on the via sidewalls. For a given applied potential the location of the transition is fixed in time and the growth front is concave in nature reflecting the gradient in chloride surface coverage. Application of a suitable potential wave form enables the location of the sidewall transition to be systematically advanced thereby giving rise to void-free filling of the TSV.